Litigation in obstetrics: does defensive medicine contribute to increases in cesarean delivery?*. (November 2014) - Cheng, Yvonne W.; Snowden, Jonathan M.; Handler, Stephanie J.; Tager, Ira B.; Hubbard, Alan E.; Caughey, Aaron B.
Abstract Objective: Obstetrics is one of the most sued subspecialties in the US. This study aimed to examine clinicians' medical-legal experience and its association with recommending cesarean delivery. Design: Cross-sectional convenience survey. Population or sample: This is a survey study of clinicians in the US. Methods: Survey included eight common obstetric clinical vignettes and 27 questions regarding clinicians' practice environment. Chi-square test, multivariable logistic regression models were used for statistical comparisons. Main outcome measures: Likelihood of recommending cesarean delivery. Results: There were 1486 clinicians who completed the survey. Clinicians were categorized based on answers to clinical vignettes. Having had lawsuits and daily worry of suits were associated with higher likelihood of recommending cesarean, compared to those without lawsuits (17.2 versus 11.3%, respectively; p = 0.008) as was frequent worry of lawsuits (every day, 20.3% more likely; every week/month, 12.3%; few times a year/never, 11.4%, p < 0.001). Conclusion: Obstetric malpractice lawsuit and frequent worry about lawsuit are associated with higher propensity of recommending cesarean delivery in common obstetric settings.